938 'TO DIP OR NOT TO DIP': IMPROVING THE MANAGEMENT OF LOWER URINARY TRACT INFECTIONS IN OLDER PEOPLE. (14th June 2022) - Muir, G
Abstract: Introduction: I completed two PDSA cycles of a Quality Improvement project, from 2019 to 2021, aimed at improving the management of lower urinary tract infections (UTIs) in older people. My interest in this subject was instilled after it was brought to my attention that Public Health England (PHE) guidelines were revised in 2018 to state that urine dipsticks tests (UDTs) should not be used as a diagnostic aid in any patient over the age of 65 years. I became concerned that geriatric patients may be misdiagnosed and mistreated with unnecessary antibiotics, given the high prevalence of asymptomatic bacteriuria in this population. Method: I sampled patients diagnosed with a urinary tract infection in the Emergency Department of the Queen Elizabeth Hospital, Gateshead over a 7-day period. I extracted medical notes of patients prescribed one of 7 antibiotics, then excluded patients under 65-years-old and those treated for an infection outside the lower urinary tract. Next, I established whether a UDT was used as a diagnostic aid using the medical notes. Results: Before and after intervention: my initial findings revealed that a UDT was performed in 100% patients diagnosed with a UTI (i.e. no cases were in line with best practice). My first educational intervention involved sharing the revised PHE guidelines with staff via an interactive teaching-session, following this I found that a UDT was performed in 62% patients. My next intervention was a flow-chart entitled 'to dip or not to dip' pasted in the ED. Following this final intervention, I found that 27% cases were in line with best practice (a UDT was used in 73% cases). Conclusion: With this modest improvement, I concluded that my recommendations reduced the number of over 65-year-old patients undergoing unnecessary UDTs as part of their diagnostic work-up.